A meta‐analysis of hospital evacuations: Overcoming barriers to effective planning. Issue 3 (January 2015) - Hicks, Jarred; Glick, Roger
<x xml:space="preserve">Abstract</x> A hospital evacuation is a significant disaster scenario facing today's Hospital Emergency Coordinators (HECs) and Risk Managers. In this work we explore the numerous barriers that prevent HECs from being able to effectively plan for and execute hospital evacuations based on a review of the pertinent literature of the last 30 years. We discuss the finding that the reasons for the success or failure generally fall into 1 or more of 8 broad categories: Predisaster Assessment, Logistics, Communications, Community Relationships, Manual Records and Tracking, Resource Management, Special Patient Populations, and Postevacuation Return.